2010
DOI: 10.1111/j.1469-0691.2009.02831.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical features of norovirus gastroenteritis in outbreaks: a population-based study

Abstract: Noroviruses are the most frequent cause of acute gastroenteritis in the community. In Catalonia, it is not clear how this type of viral gastroenteritis is evolving, and the objective of this prospective population-based study was to describe the incidence and epidemiological and clinical features of outbreaks of acute gastroenteritis due to norovirus in Catalonia between October 2004 and October 2005. Incidence rates were calculated using the estimated population of Catalonia in 2005. For each outbreak, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
2
35
0
3
Order By: Relevance
“…Noroviruses (NoVs) are widely recognized as the leading cause of human acute viral gastroenteritis worldwide (Arias et al 2010). Approximately, 20 million cases of acute gastroenteritis in the USA are related to NoV infections, as reported by the centers for disease control (CDC) (CDC2013).…”
Section: Main Text Backgroundmentioning
confidence: 99%
“…Noroviruses (NoVs) are widely recognized as the leading cause of human acute viral gastroenteritis worldwide (Arias et al 2010). Approximately, 20 million cases of acute gastroenteritis in the USA are related to NoV infections, as reported by the centers for disease control (CDC) (CDC2013).…”
Section: Main Text Backgroundmentioning
confidence: 99%
“…4,5 It is reported that in the USA annually 23 million people get infected with norovirus. 12 The main route of infection in these outbreaks it is reported to be through food and rarely through water. 9 From the 348 Norovirus outbreaks reported to the CDC between 1996-2000, 39% were foodborne, 12% from person to person contact and 3% water-borne.…”
Section: Discussionmentioning
confidence: 99%
“…14 Norovirus outbreaks are usually seen in autumn-winter period, especially between JanuaryMarch. 12 It is considered that excessive rainfall in this season is a reason of water contamination. This outbreak emerged in a rainy spring season, and it was considered that the rain along with water network repairs facilitated the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…W badaniu przeprowadzonym w Hiszpanii w czasie epidemii norowirusowych w latach 2004-2005 bóle głowy stwierdzano częściej u pacjentów pediatrycznych [28]. Bóle głowy występowały u ponad 30% dzieci w wieku do 4 lat, 40% dzieci w wieku 5-11 lat oraz 57% dzieci w wieku 12-17 lat [28]. Pacjenci poniżej 18. roku życia objaw ten zgłaszali częściej niż gorączkę i znacznie czę-ściej niż bóle mięśniowe.…”
Section: Zakażenia Przewodu Pokarmowegounclassified
“…Pacjenci poniżej 18. roku życia objaw ten zgłaszali częściej niż gorączkę i znacznie czę-ściej niż bóle mięśniowe. U osób dorosłych do 64. roku życia wszystkie powyższe dolegliwości stwierdzano około 40% pacjentów [28]. W badaniu duńskim z lat 2009-2010, w którym oceniano objawy kliniczne w infekcjach spowodowanych bakteriami z rodzaju Campylobacter u dzieci częstość występowania bólu głowy wahała się między 46% a 65%, w zależności od gatunku bakterii [27].…”
Section: Zakażenia Przewodu Pokarmowegounclassified